Analisis Kualitas Pelayanan Publik Di Kepolisian Resor (Polres) Magelang Kota - Dewi Ontro Wulan; Tri Asih Wismaningtyas; Alfina Damayanti; Anggun Larasati (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2022)
The government has a duty to provide optimal public services for the community. As part of the government, the Magelang City Police is tasked with realizing internal security which includes the maintenance of public security and order, order and law enforcement, the implementation of protection, protection, and service to the community, as well as the establishment of public peace by upholding human rights. This study aims to analyze the existing public services at Polres Magelang City. The approach used in this research is a qualitative approach with data collection techniques, namely in-depth interviews, participant observation and documentation studies. The results obtained are that the Magelang City Police has carried out its role as a public servant by continuing to make improvements and improve the quality of service. This can be seen from the service quality indicators, namely reliability, responsiveness, assurance, empathy and tangibles. Although there are several things that must be addressed, such as in terms of infrastructure and the provision of public services that are not the same.